2005
DOI: 10.1620/tjem.206.237
|View full text |Cite
|
Sign up to set email alerts
|

Priming Effect of Misoprostol on Estrogen Pretreated Cervix in Postmenopausal Women

Abstract: [237][238][239][240][241] Misoprostol, which is a prostaglandin E1 analogue, is effectively used in cervical priming in women both for labor induction and for gynecological procedures. Although its efficacy is well documented in reproductive age women, during postmenopausal period this efficacy is limited probably due to estrogen deficit. Our objective is to evaluate if estrogen deficit in postmenopausal women is important for the effect of misoprostol on cervical ripening before diagnostic procedures. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…It was concluded that misoprostol alone was ineffective for cervical ripening but it was effective in 22 women as they had used estriol vaginal cream for 14 days prior to dilatation. 7 The types of side effects were comparable in both the groups, consistent with the findings of previous studies. 6 However the frequencies of side effects were slightly more in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was concluded that misoprostol alone was ineffective for cervical ripening but it was effective in 22 women as they had used estriol vaginal cream for 14 days prior to dilatation. 7 The types of side effects were comparable in both the groups, consistent with the findings of previous studies. 6 However the frequencies of side effects were slightly more in our study.…”
Section: Discussionsupporting
confidence: 90%
“…6 Various studies in premenopausal women have shown misoprostol is a cheap alternative to laminaria tent whereas in post menopausal women it failed to show the similar benefit. 7 As far as the route is concerned both oral and vaginal has similar efficacy rate. Few studies have shown sublingual route is more effective when compared with vaginal and oral for pregnancy termination.…”
mentioning
confidence: 99%
“…References from identified publications were manually searched and cross-referenced to identify additional relevant articles. The studies have shown different cervical response and outcomes 1318. In our previous study4 we found that 1000 micrograms of self-administered vaginal misoprostol at home at least 12 hours prior to operative hysteroscopy was effective, safe and acceptable for cervical priming in premenopausal but not in postmenopausal women.…”
Section: Introductionmentioning
confidence: 98%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Most of the studies have separately, but not systematically, compared the effect on different groups of women, such as nulliparous women and postmenopausal women. Eight of the studies included less than 50 women, 12,13,16,18,[20][21][22]25 four did not compare the effect of misoprostol with a placebo, [23][24][25]27 and ten of the trials appear to be underpowered or lacking a sample size calculation as regards to evaluating primary outcome measures. [11][12][13][16][17][18][20][21][22]26 It appears that none of the trials has been designed and conducted in accordance with the CONSORT statement.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27] Less commonly, preoperative ripening is assessed by measuring cumulative dilatation force using a cervical tonometer. 11,13,16 Cervical resistance to dilatation or complications encountered during the procedure are also parameters that can indicate effectiveness of cervical ripening.…”
Section: Introductionmentioning
confidence: 99%